Experimenting on a Small Planet A Scholarly Entertainment - Hay, William W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is an introduction to climate science and global change. It includes the scientific background in physics, chemistry and biology. The science chapters are interleaved with biographical material including personal reminiscences. The science chapters discuss the history of development of ideas in geology, the discovery of Earth$1 (Bs very different climates in the distant past, and the climate oscillations of the ice ages. Special treatment is given to past warm climates. The role of greenhouse gases in controlling Earth$1 (Bs climate, along with a discussion of the associated physics. It develops the idea that humans have played a role in climate change throughout the past few millennia, rather than just since the beginning of the industrial revolution. It concludes by introducing the idea that the result of the present perturbation may be the transition to an ice-free warm world.s
The Language of Science -- Geologic Time -- Putting Numbers on Geologic Ages -- Discovering Past Climate Change -- The Nature of Energy Received from the Sun - The Analogies with Water Waves and Sound -- The Nature of Energy Received from the Sun - Figuring out what Light really is -- Exploring the Electromagnetic Spectrum -- The Origins of Climate Science - The Idea of Energy Balance -- The Climate System -- What's at the Bottom of Alice's Rabbit Hole? -- Energy from the Sun - Long-term Variations -- Solar Variability -- Albedo -- Air -- HOH - The Keystone of Earth's Climate -- Greenhouse Gasses -- The Circulation of Earth$1 (Bs Atmosphere and Ocean -- The Biological Interactions -- Sea level -- Global Climate Change - the (Geologically) Immediate Past -- Is there an Analog for the Future Climate? -- The Instrumental Temperature Record -- What is Expected in the 21st Century -- Beyond 2100 - The Return to Warm Earth -- Titanic Timeline.s
Keywords: Geography; Geology; Life sciences; Climatic changes; Earth Sciences; Climate Change; Popular Science in Nature and Environment; Earth System Sciences; Historical Geology; Geology